PENERAPAN MODEL INTRODUCTION-CONNECT- APPLY-REFLECT-EXTEND (ICARE) PADA MATERI REAKSI REDOKS DI KELAS X - Ratu Fazlia Inda Rahmayani; Ade Ismayani; Annisa Astika (Lantanida Journal, 2019)
Research on the application of the ICARE learning model to the redox reaction material in class X was done. The purpose of the study was to determine the activities and responses of students to the ICARE model. This study uses a quantitative approach. This type of research was a quasi-experiment. The research subjects were 25 students of class X MIA 1. The instruments used in the study were the students' activity observation sheets and questionnaire responses sheets. The results of observations of the activities of experimental class students at the first meeting were 83.65% and 92.19% at the second meeting. Students' responses to the application of the ICARE  model on the redox reaction material were said to be very amenable to the percentage of 85.20%. Thus it can be concluded that the application of the ICARE model can increase activities and respond very well by students in the learning process so that this model can be used in the learning process on redox reaction materials.